The Contribution of Pancasila and The Medina Charter Value in Edifying Pesantren - Aminah Aminah (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2019)
The current latent upheaval of national conditions requires Muslims to have a strong foundation and character of movement. Pancasila (the Five Principles) ideology as a pillar of movement characterized by Bhinneka Tunggal Ika (the spirit of unity in diversity), so far has contributed greatly to harmony and peace in the Republic of Indonesia. The nation's independence could not be separated from the sacrifices of the ulamas, the Islamic ummah, the heroes of various religions, and the spirit of patriotism of the Indonesian people at that time. In addition, the majority of Muslims in Indonesia must be a great force in maintaining the integrity of the nation. The method of unifying all the different backgrounds has been exemplified by the figure of Islam, the Prophet Muhammad p.u.b. with the formation of